Cognitive‐behavioural therapy for schizophrenia: A critical commentary on the Newton‐Howes and Wood meta‐analysis. (14th May 2013) - Hutton, Paul
<x xml:space="preserve">Abstract</x> Newton‐Howes and Wood (published online, this journal, 8 Dec 2011) report the results of their systematic review and meta‐analysis of clinical trials of cognitive‐behavioural therapy (CBT) for schizophrenia. They ran a random effects analysis of endpoint data from trials where participants were randomly allocated to receive either CBT or a control therapy, which could be inactive (e.g., befriending) or active (e.g., analytic supportive psychotherapy), found no difference between the groups and concluded 'it (CBT) does not outperform supportive therapy in effecting change in phenomenology.' Such a conclusion is premature, if not unwarranted, for a number of reasons, including basic mistakes, lack of transparency, and failure to consider dose.